A new position in α-RbAg4I5 at room temperature by molecular dynamics simulations. Issue 5 (23rd March 2020) - Burbano, J. C.; Correa, H.; Peña Lara, D.
ABSTRACT: By using a four-interaction interionic potential, constant-energy (classical microcanonical ensemble) molecular dynamics simulations, at room temperature, A g + ionic positions in α -RbAg4 I5 compound are reported. In this crystal structure (cubic with a  = 11.23934(3) Å and P41 32 as space group) a new site has been found. The unit cell has 16- A g + ions, and its disordered partial occupancies have been the subject of discussion. Some authors report 72 [ = 24( e ) + 24( e ) + 8( c ) + 4( b ) + 12( d ) or Ag1, Ag2, Ag3, Ag4, Ag5 ] sites with equal vacancy probabilities (Bradley and Greene), 60 [ = 24( e ) + 24( e ) + 8( c ) + 4( b ) or Ag1, Ag2, Ag3, Ag4 respectively] with different probability (Geller), 56 [ = 24( e ) + 24( e ) + 8( c ) + 4( b ) or Ag1, Ag2, Ag3 ] with different probability and 4 sites having zero probability (Hull et al ). We report 96 interstitial sites [ = 24( e ) + 24( e ) + 8( c ) + 4(b) + 12( d ) + 24( e ) or Ag1, Ag2, Ag3, Ag4, Ag5, Ag6, respectively] with different probabilities. The new site was denoted as Ag6 with 0.77% similar to Ag5 (∼0.66%). Good results (occupancy probabilities) compared to experimental data were found.